Studying the effect of heterosis and predicting the prospects of hybrid spring wheat populations in breeding for productivity and drought resistance - L. V. Volkova; O. S. Amunova (Труды по прикладной ботанике, генетике и селекции)
Background. In combination breeding, information about the degree of superiority of hybrids in productivity and drought resistance over their parents in early generations, as well as the possibility of preserving their advantages in subsequent generations, are of great practical interest.Materials and methods. In 2018–2021, 16 hybrid populations of spring bread wheat of the 1st through 4th generations, obtained from intraspecific crosses among parent cultivars, were studied at the Federal Agricultural Research Center of the NorthEast. The hybrids and their parents were tested in the field for productivity and in the laboratory for drought resistance. Inheritance types were determined by the degree of phenotypic dominance of plant characters. Statistical processing of the results was carried out using correlation and variance analyses.Results. Hybrids that demonstrated heterosis in the number of grains per ear had an advantage on this basis in subsequent generations. The inheritance type of the 1000 grain weight did not determine the level of this character in older generation hybrids. There was a change in the type of inheritance for the number of radicles during the transition from normal to stressful conditions. Hybrids that showed heterosis in seedling weight in the control and the experiment were distinguished by higher rates in subsequent generations. A significant negative correlation was found between grain yield and the number of radicles formed with a lack of moisture, and a positive correlation between grain yield and the weight of seedlings. Seven promising hybrid combinations fusing productivity with drought resistance were identified.Conclusion. The analysis of hybrids from early generations according to the degree of phenotypic dominance of the number of grains per ear and number of radicles in the experiment, and the weight of seedlings in the control and the experiment can be quite informative for use in breeding programs.